Carrier Interfacial Engineering by Bismuth Modification for Efficient and Thermoresistant Perovskite Solar Cells. Issue 20 (25th March 2018) - Chen, Cong; Liu, Dali; Zhang, Boxue; Bi, Wenbo; Li, Hao; Jin, Junjie; Chen, Xu; Xu, Lin; Song, Hongwei; Dai, Qilin
Abstract: Organic–inorganic halide perovskite solar cells (PSCs) have emerged as attractive alternatives to conventional solar cells. It is still a challenge to obtain PSCs with good thermal stability and high permanence, especially at extreme outdoor temperatures. This work systematically studies the effects of Bi 3+ modification on structural, electrical, and optical properties of perovskite films (FA0.83 MA0.17 Pb(I0.83 Br0.17 )3 ) and the performance of corresponding PSCs. The results indicate that Bi 3+ modified PSCs can achieve better thermal stability, photovoltaic response, and reproducibility compared with control cells due to the decreased grain boundaries, enhanced crystallization, and improved electron extraction from perovskite film. As a result, the modified PSC exhibits an optimized power conversion efficiency (PCE) of 19.4% compared with 18.3% for the optimized control device, accompanied by better thermoresistant ability under 100–180 °C and enhanced long‐term stability. The degradation rate of the modified device is reduced by an order of magnitude due to effective structural defect modification in perovskite photoactive layer. It could maintain more than two months at 60 °C. These results shed light on the origin of crystallization and thermal stability of perovskite films, and provide an approach to solve thermal stability issue of PSCs. Abstract : Bi 3+ modification in the perovskite photoactive layer is shown to induce a higher energy barrier for decomposition, resulting in an excellent thermoresistant ability of 80–180 °C and long‐term stability of 2500 h in ambient conditions. The modified devices exhibit an optimized PCE of 19.4% and maintain activity for more than two months. This provides an approach to solve the thermal stability issue of perovskite solar cells.